Analysis of Boeing Aircraft’s Fuel Consumption B737-800 NG for Yogyakarta-Singapore-Jakarta Route - Suar Ishak; Elisa Kusrini (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2020)
AbstractIn one trip, the flight route can be seen in terms of weight, cargo, and the price of fuel needed as a very important aspect. Fuel prices that are high enough can have an impact on operational costs that were incurred by an airline. The purpose of this study was to avoid re-fueling at the re-fueling stations that cost more than the original station. This study used the fuel tankering method, and also focused on the Garuda Indonesia flight B737-800 NG airline with Jogyakarta-Singapore-Jakarta route and alternative airports at Pekanbaru and Surabaya. From the results of the data that was obtained and the analysis the result of this study was by refueling using the fuel tankering method was more profitable than normal way of re-fueling. However, there were aspects that need to be considered in the route using this method including temperature, altitude, flight distance and fuel prices that were differrent at each airport.Keywords: Route, Fuel Price, fuel tankering method.